Peningkatan Kemampuan Berpikir Kritis Siswa pada Pembelajaran Agama Katolik Melalui Model Pembelajaran Probing-Prompting Pada Fase D Di SMP Santo Antonius Bangun Mulia - Sitepu, Helena; Sihotang, Din Oloan; Waruwu, Ermina (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
Critical thinking skills are vital for students' intellectual development. This article examines the importance of critical thinking in education, focusing on factors influencing students' abilities and effective learning methods to enhance them. The study evaluates students' critical thinking abilities before and after using the Probing-Prompting learning model at Santo Antonius Bangun Mulia Middle School, Medan. This model was chosen for its ability to stimulate thinking processes and develop critical thinking skills. Key indicators for measuring critical thinking abilities, such as analysis, evaluation, inference, explanation, and skepticism, are discussed. The article also explores internal and external factors affecting these abilities. The Probing-Prompting model is described as stimulating students' thinking through a series of problem-solving questions, detailing the interactions between teachers and students. The research, conducted through classroom action research (PTK) with two cycles, involved 26 class VII students. Results show an increase in students' critical thinking abilities after implementing the model. These findings aim to contribute to theoretical understanding and offer practical benefits for educators to improve education quality.